Recent Publications (Quarterly Journal of Economics, 1957)
Recent Publications Get access The Quarterly Journal of Economics, Volume 71, Issue 4, August 1957, Pages 639–642, https://doi.org/10.1093/qje/71.4.639 Published: 01 August 1957